An initial study of the dynamic influences and interactions upon levels of sustainability at the global spatial scale. (December 2022) - Phillips, Jason
This paper conducts an initial determination and evaluation of the fundamental dynamic influences and interactions upon indicated levels and nature of sustainability occurring, at the global spatial scale over the specified period of 2006–2016. This is achieved by the first full application of the Sustainability Dynamics Framework (SDF) to the results of the Sustainable Society Index (SSI). The results indicate that obtainedS -values are potentially influenced primarily by a triumvirate of influencing factors – Population Growth, GDP and Greenhouse Gases. A cumulative analysis of indicator categories indicated that Environmental Wellbeing was the dominant influencing category upon obtained S-values for the period 2008–2014, and Anthropospheric Wellbeing was the dominant influence in 2006 and 2016. The analysis concludes that the triumvirate has potentially caused fundamental breaches and dynamic impacts and feedbacks upon the global environment-human relationship and system. Unless the triumvirate is managed and mitigated urgently, then there is a potential realistic risk of unsustainability occurring.